Optimization of Carbon Dioxide Foam Fracturing Technology for Shale Gas Reservoir - Chaoli Gao; Shiqing Cheng; Mingwei Wang; Wen Wu; Zhendong Gao; Song Li; Xuangang Meng (Geofluids)
Major shale gas exploration and development fields are located in the Sichuan basin. It requires huge water sources for shale gas fracking, but the well sites are mostly in the hills, which limits the industrialization of shale gas development. CO2 foam fluids can meet the requirements of fracking fluids and relieve water stress. It analyzed the feasibility of CO2 foaming fracturing for shale gas formation fracturing, proposed a design philosophy for CO2 foaming fracturing, and optimized fracturing parameters such as foam mass, proppant concentration, friction, and discharge rate. The flowchart of CO2 foam fracturing was established in, where the fracture morphology and propagation behavior of CO2 foam fracturing were obtained from numerical simulations comparable to the hydraulic fracture generated by conventional hydraulic fracturing. The CO2 foaming fracturing technique can provide a discharge rate of 6.0 m3/min and fluid volume and captures the volume effect of the current stimulated reservoir, which needs to be improved. It can be considered an initial survey of CO2 foam fracturing available in the Sichuan Basin shale formation, which may provide new methods and clues for stimulation.